The Insubstantial and Exclusionary Nature of Plato’s Aesthetic Theory - Alcock, Nicholas James (Stance: an international undergraduate philosophy journal, 2014)
In this paper, I argue that Plato’s conversance with art is insubstantial and exclusionary. Art warrants not only subjects in virtue of utility, morality, and pleasure, but also subjects in virtue of feeling, impression, spirituality, and art itself. I will begin by providing Plato’s view and then provide my threefold objection, utilizing examples from art history and the history of aesthetic theory.